The Changing Role of Tax Governance: Remaking the Large Corporate Taxpayer into a Visible Customer Partner. (7th August 2013) - Tuck, Penelope
Abstract : Neo‐liberalism encourages the rule of private interests coordinated by markets and arms'‐length regulation by central government and regulatory bodies, and also through the explosion of audit and scrutiny. Part of this approach is the reconceptualization of users of services or functions as customers even though a quasi supplier relationship does not seem to be involved, such as between a regulator and a regulatee. This empowerment of the customer has a consequential impact on the regulation process. This paper theorizes this dynamic of power as recursive governmentality. It examines the change and unintended consequences in a regulatory authority, HM Revenue and Customs, the UK tax administration, as it responds to this policy context and how this leads to a search for a new identity as a customer‐service provider.